Study on temperature field characteristics of window glass unexposed surfaces under varying indoor fire source conditions - Zhihan Li; Guowei Zhang; Longfei Yu; Yinxin Qu; Xiangfei Liu (Case Studies in Thermal Engineering, 2025)
This study developed a full-scale indoor fire test platform to investigate the feasibility of fire source localization through inverse analysis of temperature fields on the fire-unexposed side of glass windows. Experimental data encompassing temperature fields and fire parameters were systematically acquired by varying fire source positions and heat release rates (HRR). Key findings revealed that all regions of the fire-unexposed glass surface exhibited near-linear temperature rise trends with thermal response delays, accompanied by significant non-uniform distribution characteristics (temperature non-uniformity coefficients >36.36 %) across different fire conditions. Increased HRR amplified spatial disparities in warming rate increments while these disparities escalated proportionally with fire intensity. Reduced normal distance between the fire source and window preferentially enhanced warming rates in lower-elevation glass regions adjacent to the ignition source, whereas decreased radial distance from the fire source to the window axis resulted in disproportionately higher warming rate increments in upper glass zones compared to fire-proximal areas. Theoretical analysis of heat flux distribution on the fire-exposed side demonstrated spatiotemporal non-uniformity, with prediction errors constrained within 24.04 %. These findings collectively confirm the technical viability of fire source localization through inverse analysis of temperature field patterns on glass surfaces.